2008
DOI: 10.1186/1471-2334-8-75
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1, HSV-2 and syphilis among pregnant women in a rural area of Tanzania: Prevalence and risk factors

Abstract: BackgroundEvidence suggests that a substantial proportion of new HIV infections in African countries are associated with herpes simplex virus type 2 (HSV-2). Thus, the magnitude of HSV-2 infection in an area may suggest the expected course of the HIV epidemic. We determined prevalence of genital herpes, syphilis and associated factors among pregnant women from a remote rural Tanzanian community that has a low but increasing HIV prevalence.MethodsWe analysed 1296 sera and responses to a standard structured ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
47
5
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 35 publications
12
47
5
1
Order By: Relevance
“…This variation could be due that sample size in the present study was larger than the previously reported one. This study HSV 2 seroprevalence (35.2%) in pregnant women was higher to that reported for Italy (7.6-8.4%) [24], China (10.8%) [26], Indonesia (9.9%) [27], Bangladesh (9.91%) [28], and UK (10.4%) [29], Tanzania (20.7%) [30], Australia (30%) [31], USA (22%) [32], Switzerland (21.2%) [33], Canada (17.3%) [34], Senegal (22%) [35], Belgium (18.2%) [36], China (23.5%) [37], and Korea (17%) [38], Turkey (4.4%-5%) [39,40], Kashmir (7.5%) [41], India (8.7%) [42], Croatia (6.8%) [43]. In contrast to our study, a much higher HSV 2 seroprevalence has been reported from Zimbabwe (51.1%) [44], Germany (82%) [45], Turkey (63.1%) [46], and Iran (43.75%) [47].…”
Section: Discussionmentioning
confidence: 84%
“…This variation could be due that sample size in the present study was larger than the previously reported one. This study HSV 2 seroprevalence (35.2%) in pregnant women was higher to that reported for Italy (7.6-8.4%) [24], China (10.8%) [26], Indonesia (9.9%) [27], Bangladesh (9.91%) [28], and UK (10.4%) [29], Tanzania (20.7%) [30], Australia (30%) [31], USA (22%) [32], Switzerland (21.2%) [33], Canada (17.3%) [34], Senegal (22%) [35], Belgium (18.2%) [36], China (23.5%) [37], and Korea (17%) [38], Turkey (4.4%-5%) [39,40], Kashmir (7.5%) [41], India (8.7%) [42], Croatia (6.8%) [43]. In contrast to our study, a much higher HSV 2 seroprevalence has been reported from Zimbabwe (51.1%) [44], Germany (82%) [45], Turkey (63.1%) [46], and Iran (43.75%) [47].…”
Section: Discussionmentioning
confidence: 84%
“…Although this seroprevalence result falls within the range of 30%-80% found among women of reproductive age in sub-Saharan Africa [11], it is higher than HSV-2 seroprevalences found in several studies among populations of pregnant women in the sub-Saharan Africa region: 20.7% and 33.6% from different locations in Tanzania [12,13]; and 26% in Senegal [14]. This figure is still remarkably higher than findings from studies on pregnant populations outside Africa: 7.5% in India [15], 11.5% in Australia [16], 14.5% in Mexico [17], and 22% in USA [18].…”
Section: Discussionmentioning
confidence: 99%
“…3,11,22 The inconsistent use of condom with their sexual partners prevailed (57.8%) among the HSV-2 sero-positive women and this was observed in similar studies on pregnant women. 7,[21][22][23][24] This is of great concern as HSV-2 transmission can occur in long-standing monogamous relationships, and the virus may be transmitted to a susceptible partner after a long time of unprotected sexual contact with an asymptomatic but infected partner. 7 There is need for consistent use of condom as nearly everyone, with genital HSV-2 infection sheds virus intermittently without symptoms.…”
Section: Discussionmentioning
confidence: 53%
“…This is in agreement with other studies, which show that HSV-2 sero-positivity is associated with a greater number of lifetime sexual partners and multiple sexual partners within six months to the time of the study. 3,7,12,[22][23][24][25][26][27][28][29] In the present study, women with more than one lifetime sexual partners were 2.4 times more likely to have HSV-2 infection than those with one lifetime sexual partner. This is similar to some other studies which observed that women with more than one lifetime sexual partners were twice as likely to have HSV-2 antibodies, than those with one partner.…”
Section: Discussionmentioning
confidence: 83%